Primary Adrenal Lymphoma with Secondary Central Nervous System Involvement: - Kübra Aydın; Kerem Okutur; Mustafa Bozkurt; Özlem Aydın; Esat Namal; Akın Öztürk; Kezban Nur Pilancı; Reyhan Diz Küçükkaya; Osman Gökhan Demir (Turkish Journal of Hematology, 2013)
Approximately 10%-20% of all systemic lymphomas have central nervous system (CNS) involvement, which has been correlated to a worsened prognosis. It is well known that secondary involvement of the adrenal glands may occur in up to 25% of patients during the course of diffuse lymphoma. Primary adrenal lymphoma (PAL), however, is a different entity, and it is defined as the presence of adrenal lymphoma without evidence of either nodal involvement or leukemia. It has been shown that this occurrence is rarely accompanied by extranodal involvement, such as in the CNS. PAL exhibits a tendency for CNS relapse and this possibility should be examined even before symptoms are present. Herein we present a patient with PAL and secondary CNS involvement.